Konsistensi Mutu Pilus Tepung Tapioka: Identifikasi Parameter Utama Penentu Kerenyahan - Rosita Hardwianti Imam; Mutiara Primaniyarta; Nurheni Sri Palupi (Department of Food Science and Technology (ITP), Faculty of Agricultural Technology, Bogor Agricultural University (IPB) in collaboration with the Indonesian Food and Beverage Association (GAPMMI), the National Agency of Drug and Food Control, and th, 2014)
The quality of nal product is important aspect of product acceptability and it is affected frequently by the quality of raw materials. Pilus is a fried round-shaped snack and is made from tapioca with a mixture of spices, then fried before it is ready to be consumed as a snack or a side dish companion. Pilus has a crispy texture. Generally, major pilus industry requires the large quantities of tapioca, but is often constrained to obtain supplier that provides consistent tapioca quality. The objective of this research was to characterize tapioca starch as raw material of pilus; to determine the testing parameters that correlate to crispness of pilus; to evaluate the consistency of tapioca starch quality from suppliers. The tested quality parameters included starch, amylose, amylopectin contents, swelling power, starch pasting profile, texture analysis and sensory quality. Tapioca starch had of 77-81% of starch, 22-28% of amylose- amylopectin ratio, 2.43-6.91% of swelling power, and 8.01- 10.67 kgf of the crispness value. The relevant parameters to specify pilus crispness were amylose amylopectin ratio and peak viscosity ofstarch pasting profiles. The quality of raw materials used in pilus processing was inconsistent.